Rumput Brachiaria decumbens : antara Manfaat dan Risiko untuk Pakan Ruminansia - Yanuartono, Y; Paryuni, A D; Soedarmanto, I (Politeknik Negeri Lampung, 2024)
Brachiaria decumbens grass is one of the grazing grasses with better production than field grass. It has high nutritional value, is more resistant in the dry season, and is suitabel for tropical areas. Brachiaria decumbens grass, called Signal Grass, is usually planted for pastures—permanent grazing, but also planted or conserved in limited quantities by smallholder farmers. The general nutritional content of Brachiaria decumbens natural grass is 10.08% water content, 14.11% ash, 3.21% crude protein, 47.39% crude fiber, 2.25% crude fat, 33.04% BETN, TDN 42.14%. Even though it has high nutritional value, Brachiaria decumbens contains anti-nutritional steroid saponin factors such as protodioscin, diosgenin, and yamogenin, which can interfere with growth and are toxic to ruminants. This article reviews the benefits and risks of using Brachiaria decumbens grass as forage for ruminant livestock.